2017
DOI: 10.1038/srep45272
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Impairment in Congenital Muscular Dystrophy Type 1A and Leigh Syndrome Muscle Cells

Abstract: Skeletal muscle has high energy requirement and alterations in metabolism are associated with pathological conditions causing muscle wasting and impaired regeneration. Congenital muscular dystrophy type 1A (MDC1A) is a severe muscle disorder caused by mutations in the LAMA2 gene. Leigh syndrome (LS) is a neurometabolic disease caused by mutations in genes related to mitochondrial function. Skeletal muscle is severely affected in both diseases and a common feature is muscle weakness that leads to hypotonia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…Finally, we measured the expression of Pgc1 α encoding peroxisome proliferator-activated receptor gamma coactivator 1α (a key regulator of mitochondrial metabolism) that we have shown to be decreased in LAMA2-CMD patient myotubes 5 . However, expression of Pgc1 α was not altered in dy 2J /dy 2J muscles and metformin did not change its expression either (Figs 6F and 7F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we measured the expression of Pgc1 α encoding peroxisome proliferator-activated receptor gamma coactivator 1α (a key regulator of mitochondrial metabolism) that we have shown to be decreased in LAMA2-CMD patient myotubes 5 . However, expression of Pgc1 α was not altered in dy 2J /dy 2J muscles and metformin did not change its expression either (Figs 6F and 7F ).…”
Section: Resultsmentioning
confidence: 99%
“…A majority of the differentially expressed genes and proteins were found to be involved in various metabolic processes 3 , 4 . Subsequently, we demonstrated functional bioenergetic impairment with reduced mitochondrial respiration and a compensatory upregulation of glycolysis in human LAMA2-CMD muscle cells 5 . Thus, from these studies, we concluded that skeletal muscle metabolism may be a promising pharmacological target to improve muscle function in LAMA2-CMD patients.…”
Section: Introductionmentioning
confidence: 92%
“…We have previously performed transcriptional and proteomic profiling of LAMA2-CMD mouse muscles and found that a majority of the dysregulated genes and proteins are involved in various metabolic processes, indicating a metabolic crisis in LAMA2-CMD muscles [9,10]. More recently, a metabolic impairment, with reduced mitochondrial respiration and enhanced glycolysis was observed in human laminin α2-chain deficient muscle cells [11]. Insufficient mitochondrial respiration in turn, enhances the formation of reactive oxygen species (ROS), which long have been suggested to be major contributors to muscle damage in dystrophic muscles [12].…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models for LAMA2-CMD have provided an excellent platform for studies of signaling events. Signaling cascades associated with apoptosis, inflammation, metabolism, regeneration, protein turnover, and fibrosis (GAPDH-Siah1-CBP/p300-p53, Akt, TGFβ, NFκB, p53, JAK/STAT, to mention a few) have been shown to be affected in laminin α2 chain-deficient murine muscle (Girgenrath et al, 2004(Girgenrath et al, , 2009Erb et al, 2009;Carmignac et al, 2011a,b;Kumar et al, 2011;Meinen et al, 2012;Elbaz et al, 2015;de Oliveira et al, 2014;Mehuron et al, 2014;Accorsi et al, 2015;Fontes-Oliveira et al, 2017;Gawlik et al, 2017Gawlik et al, , 2019Nunes et al, 2017;Pasteuning-Vuhman et al, 2018;Yoon et al, 2018). Additionally, microarray, RNA-sequencing and proteomic technologies were applied to study murine LAMA2-CMD dystrophic muscle and provided a global overview of the gene and protein expression changed upon laminin α2 chaindeficiency (van Lunteren et al, 2006;Hager et al, 2008;de Oliveira et al, 2014;Kemaladewi et al, 2017;Moreira Soares Oliveira et al, 2018;Yanay et al, 2019).…”
Section: Cellular and Molecular Events In Murine Laminin α2 Chain-defmentioning
confidence: 99%